A great leap of faith: The cashless agenda in Digital India. (August 2019) - Athique, Adrian
This article assesses the rationale for India's November 2016 demonetization, in terms of its origins and impact over the following year. I argue that this intervention was conceived and understood as part of a larger international monetary experiment. The article draws upon international media commentary, impact assessments by Indian scholars and the professed goals of the Government of India. Having established a direct link between demonetization and an advancing 'cashless agenda' around the world, I situate Narendra Modi's Digital India programme as the putative foundation for a transactional economy. Drawing upon ethnographic studies exploring the everyday experience of India's year of living digitally, this article raises the critical question of who must, or indeed can, bear the transaction costs of this digital utopia. In conclusion, I argue that the rapid expansion of digital money situates these concerns at the heart of social and cultural, as much as economic, analysis.